If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 + 2x = 10x + -1 Reorder the terms: 4 + 3x + 2x = 10x + -1 Combine like terms: 3x + 2x = 5x 4 + 5x = 10x + -1 Reorder the terms: 4 + 5x = -1 + 10x Solving 4 + 5x = -1 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 4 + 5x + -10x = -1 + 10x + -10x Combine like terms: 5x + -10x = -5x 4 + -5x = -1 + 10x + -10x Combine like terms: 10x + -10x = 0 4 + -5x = -1 + 0 4 + -5x = -1 Add '-4' to each side of the equation. 4 + -4 + -5x = -1 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = -1 + -4 -5x = -1 + -4 Combine like terms: -1 + -4 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| ln(x+2)=ln(x-7)+ln(4) | | (-2n^2+8n+2)(7n^2-4n-5)= | | 2y^2+10y+25=0 | | 2(B+6)+5B=40 | | u=16+5*16-0.12*16*16 | | -7x-3=-21 | | ln(x+2)-ln(x-7)=ln(4) | | Y=-1(3x-1) | | Y=1(x-1) | | 15x^4-120x^2+240=0 | | x+.04x=23750 | | 25+q^2=2q^2 | | u=16+5*14-0.12*14*14 | | x+.04=23750 | | -x+(x-4)=2 | | 95=6x+9 | | 0=x^2+3x-38 | | 8-7(4-w)=10w-(3w-5) | | xy+5x+2y=5 | | 2x-12=8-3x | | a=6x^2*3x^4 | | 3x-1(x+1)=3x-7 | | -2(y+4)+6y=(y-3) | | (W)+(W-4)=32 | | -4(-3w+2)-w=3(w-5)-7 | | 4(5x-6y)-(4x-7y)= | | 18x+15y+8z=0 | | 4(5x-6y)-(4x-9y)= | | -2(-0.75)+3=y | | 5(10*x+3)+3(1-3*x)=0 | | y=x*x+x*x-5 | | x=2+3*4 |